2021
DOI: 10.1177/00812463211001530
|View full text |Cite
|
Sign up to set email alerts
|

Current strategies in the reduction of stigma among caregivers of patients with mental illness: a scoping review

Abstract: Mental healthcare and wellness are a global concern and have increasingly become an essential service and priority from a human rights perspective. However, negative attitudes towards mental health, such as stigmatisation and discrimination from communities and family members, continue to pose challenges for deinstitutionalisation and home care of mentally ill persons. This study aimed to review the literature on the content and implementation methods of stigma reduction interventions for family/community care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Several other studies have reported high implicit stigma among family members of mental health service users (González-Sanguino et al, 2019;Singh et al, 2016;Tawiah et al, 2015;Zhang et al, 2018). Given the continued prevalence of mental health stigma, especially in African communities, it is understandable how non-disclosure is an appealing stigma prevention strategy (Abdullah & Brown, 2011;Dako-Gyeke & Asumang, 2013;MacGregor, 2018;Mavundla et al, 2009;L. H. Yang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several other studies have reported high implicit stigma among family members of mental health service users (González-Sanguino et al, 2019;Singh et al, 2016;Tawiah et al, 2015;Zhang et al, 2018). Given the continued prevalence of mental health stigma, especially in African communities, it is understandable how non-disclosure is an appealing stigma prevention strategy (Abdullah & Brown, 2011;Dako-Gyeke & Asumang, 2013;MacGregor, 2018;Mavundla et al, 2009;L. H. Yang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organisation (WHO) developed the 2019-2023 Special Initiative for Mental Health to reiterate the significance of comprehensive, integrated, and responsive community-based mental health services (WHO, 2019). These global efforts aim to build on the momentum and progress achieved to date, especially in developing countries where funding for mental health services remains constrained (Monnapula-Mazabane et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intervention covered five critical topics for caregivers that addressed common misconceptions about mental illness: general mental health education, mental health stigma, communication and behaviour management, caregiver well-being, and coping strategies. The selection of the topics was based on a recent review of mental health anti-stigma interventions in LMICs, 21 contextualised and informed by a formative study conducted within our study population. 15 Development of the training manual and considerations for training facilitators were guided by adult learning principles.…”
Section: Intervention Descriptionmentioning
confidence: 99%
“…20 A recent review on stigma reduction interventions in LMICs identified only nine studies that varied in their educational content, and only three explicitly included stigma sessions. 21 The deinstitutionalisation of mental health services requires community-level anti-stigma interventions to accompany this process to aid the reintegration of service users within their communities, inclusive of service users themselves, caregivers and their families. Therefore, our study qualitatively evaluated the feasibility and acceptability of a community-delivered mental health intervention for family caregivers from low-income South African communities.…”
Section: Introductionmentioning
confidence: 99%